Identifying barriers and solution strategies for retailers’ adoption of virtual reality shopping– an experts’ perspective - Elsholz, Sophia; Nguyen, Danny; Zarnekow, Rüdiger (Frontiers in Virtual Reality, 2025)
Despite the potential advantages of virtual reality (VR) shopping in providing novel and immersive user experiences, retailers are reluctant to implement actual applications. Current commercial applications are more akin to marketing instruments than actual stores with purchase possibilities, revealing that current potentials are yet to be recognized by the market. However, research concerning the retailers’ perspective is scarce. The present article thus seeks to identify reasons for the market’s reluctance and to propose potential solutions. Based on the technology-organization-environment (TOE) model and several TOE-related theories, such as the Diffusion of Innovation, we conducted interviews with market experts that revealed the most salient factors for the reluctance, including the cost of the technology, unrecognized values for customers, and the high implementation expenses for organizations. Our research contributes to the ongoing discourse on the potential of virtual reality to shape humans’ digital lives by revealing several barriers and solution strategies for the introduction of VR retail applications.